Dampak Digital Marketing Terhadap Purchasing Decisions: Studi Kasus Generasi Milenial - Diah Kusumawati; Edwin Zusrony; Wesly Tumbur ML Tobing (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to find the influence of mobile marketing, social media marketing, and internet advertising on purchasing decisions in e-commerce. This research is quantitative, and the study population consists of millennial generation e-commerce users living in Salatiga city. This study used purposive sampling in which 70 respondents were selected. This study applies multiple linear regression, which is one of the data processing techniques, and the data were analyzed using SmartPLS 4.0. The findings of this study, mobile marketing separately has a positive but not statistically significant influence on purchasing decisions, while social media marketing and online advertising have a positive and statistically significant influence on purchasing decisions. In the multiple regression analysis where the independent variables are mobile marketing, social media marketing, and online advertising, the dependent variable is e-commerce purchasing decisions, which is found to have a positive and statistically significant influence.